Zero-sequence current injection theory and injection-based coil tuning in compensated distribution networks - Siermala, Saku (My University, 2023)
This thesis aims to derive and document zero-sequence current injection theory in compensated distribution networks. More specifically, the objective is to derive a comprehensive set of equivalent circuits and equations that describe the primary interactions between the current injection and system parameters. The auxiliary zero-sequence current injection is an essential method addressing various complex applications in compensated networks, including tuning arc suppression coil, detecting high impedance faults, locating earth faults, and residual earth fault currents compensation. This thesis explicitly considers the current injection when current is injected into the zero-sequence system through the network’s neutral point via the power auxiliary winding of the arc suppression coil. The theoretical part of the thesis introduces the fundamentals of compensated networks, including system damping, detuning, unbalance, and their influence on the natural zero-sequence voltage. Regarding the current injection, the idea, implementation, and key applications of the concept are presented, including the derivation of injection theory that describes the phenomenon. The injection theory defines the impact of current injection on a compensated network by deriving relevant equations and equivalent circuits that describe the system’s response to the injection and the parameters affecting it. The injection theory is also verified and visualized using PSCAD and MATLAB software. Additionally, the thesis includes a literature review on commercial injectionbased coil tuning solutions. Current injection is an attractive method for arc suppression coil tuning, enabling operation in fully symmetrical networks and faster tuning without additional coil movements. The scope of the review focuses on the following well-known products: current injection device ECI by Trench Group, Current Injection for Low or Highly Variable Zero-Sequence Voltages by A. Eberle Gmbh & Co.KG, and Multi-Frequency Current Injection by A. Eberle Gmbh & Co.KG and EGE spol. s r.o. The review aims to describe the design and functionality of the previous products and highlight the key differences and advantages of the different solutions. The source material of the review includes product data sheets, scientific publications, and related patents. In total, the result of the thesis is an extensive collection of current injection theory, including equations, graphs, and equivalent circuits describing the phenomenon. Moreover, the thesis provides a comprehensive literature review on commercial injection-based coil tuning solutions. Tämän diplomityön tavoitteena on virtainjektioteorian selvittäminen, johtaminen ja dokumentointi kompensoiduissa sähkönjakeluverkoissa. Erityisesti työn tavoitteena on tuottaa kattavat virtainjektiota kuvaavat sijaiskytkennät ja yhtälöt, jotka määrittelevät pääasiallisia vuorovaikutuksia injektion ja verkon järjestelmäparametrien välillä. Virtainjektio on olennainen menetelmä, jota sovelletaan moniin haastaviin sovelluksiin kompensoiduissa verkoissa, kuten kompensointikelan viritys, suuri-impedanssisten vikojen havainnointi, maasulun paikantaminen ja jäännösmaasulkuvirran kompensointi. Tässä työssä virtainjektiota käsitellään erityisesti, kun virtaa syötetään järjestelmän nollajärjestelmään kompensointikelan tehoapukäämin kautta. Työn teoriaosuudessa käsitellään kompensoitujen verkkojen perusteoriaa, mukaan lukien järjestelmän vaimennusta, vinoviritystä ja epäsymmetriaa sekä niiden vaikutus verkon luonnolliseen nollajännitteeseen. Virtainjektion osalta esitetään konseptin idea, toteutus ja keskeiset sovellukset sekä johdetaan ilmiötä kuvaava virtainjektioteoria. Virtainjektioteoria määrittää injektion aiheuttaman vaikutuksen verkkoon, sisältäen johdetut yhtälöt ja sijaiskytkennät, jotka kuvaavat järjestelmän vasteen injektioon ja tuovat esiin siihen vaikuttavat parametrit. Johdettu injektioteoria verifioidaan ja visualisoidaan hyödyntäen PSCAD ja MATLAB ohjelmistoja. Lisäksi työ sisältää kirjallisuuskatsauksen kaupallisiin virtainjektioperusteisiin kompensointikelan säätömenetelmiin. Virtainjektion käyttö kelan säädössä onkin suosittu menetelmä, koska se mahdollistaan toiminnan täysin symmetrisissä verkoissa ja nopeamman virityksen ilman ylimääräisiä kelan liikkeitä. Tarkemmin katsauksessa keskitytään seuraaviin tunnettujen valmitajien tuotteisiin: Trench Group:n virtainjektori ECI, A. Eberle Gmbh & Co.KG:n virtainjektiolaitteisto pienille tai erittäin vaihteleville nollajännitteille, A. Eberle Gmbh ja Co.KG:n and EGE spol. s r.o:n yhdessä kehittämä monitaajuusvirtainjektiolaite. Katsauksen tavoite on kuvata tuotteiden toimintaa ja toimivuutta sekä tuoda esiin eri ratkaisujen keskeiset erot ja edut. Lähdeaineistona käytetään tuotteiden datalehtiä, tieteellisiä julkaisuja ja aiheeseen liittyviä patentteja. Kokonaisuudessaan diplomityön lopputuloksena on laaja kokoelma virtainjektioteoriaa, sisältäen ilmiötä kuvaavia yhtälöitä, kuvaajia sekä sijaiskytkentöjä. Lisäksi opinnäytetyö tarjoaa kattavan kirjallisuuskatsauksen kaupallisista injektioperusteisista kelan säätöratkaisuista.
Keywords: fi=Sähkötekniikka|en=Electrical Engineering|; fi=Energia- ja informaatiotekniikan ohjelma|en=Degree Programme in Energy Technology and Information Technology|; Sähkötekniikka